(untitled) (Journal of Academic Research, 2024)
One of the most important things that can be taken care of and studied is the investigation of the books and fatwas of our evacuation scholars, because of their great value on the religious and heritage level. It highlights and shows the extent of their mastery of Islamic sciences, as it is the true witness to their role that they contributed to the victory, spread and preservation of the constants of religion, and their contribution to the spread of Islamic civilization in its best form, and in view of the scientific, jurisprudential and linguistic value that this manuscript bears. Where the research discusses an important topic related to the personal status that may affect every person, In its investigation, it relied on a set of sources and references, both ancient and contemporary, to show the research as correctly and soundly as possible.